(untitled) (Scientific journal of the Fergana State University, 2023)
This article covers the issues of the current state and the main trends in the mortality of the elderly and senile population in Ferghana region. As a statistical material for processing, the data of a continuous retrospective study were taken from the reporting materials of tables C42, C45, C51 of the statistics department of Ferghana region.